The Influence of Sharia Compliance Dimensions on Sharia Standard Implementation in Beauty Care Services - Andi Faradilla; Rahma Hidayati Darwis; Fitriani Fitriani (Management Department Universitas Islam Negeri Sumatera Utara, 2026)
The rapid growth of the halal beauty industry has increased the demand for beauty services that comply with Islamic principles. However, empirical studies examining sharia compliance at the organizational level of beauty service providers remain limited. This study aims to analyze the influence of three dimensions of sharia compliance, namely product halalness, service ethics and aurah protection, and spiritual values and sharia branding, on the implementation of sharia standards at Arnhilah Aesthetic Care Clinic. A quantitative approach was employed using a survey of 101 clinic customers selected through accidental sampling. Data were analyzed using multiple linear regression with SPSS. The results indicate that product halalness has the strongest positive and significant effect on sharia standard implementation (β = 0.602; p < 0.001), followed by service ethics and aurah protection (β = 0.173; p = 0.023). Spiritual values and sharia branding also demonstrate a positive effect, although with marginal significance (β = 0.183; p = 0.050). Simultaneously, the three dimensions explain 49.4% of the variance in sharia standard implementation. These findings suggest that comprehensive implementation of sharia standards requires the integration of halal product assurance, ethical service practices, and authentic Islamic organizational values. The study contributes to the development of multidimensional sharia compliance assessment in beauty service organizations. Keywords: Halal Cosmetics, Islamic Business Ethics, Sharia Compliance, Sharia Standard Implementation